Genetic model of the Kara formation (Lower Carbonniferous) ofNorth-Easternpartofthe ridge of Pai-Khoi - K. P. Ryazanov (Известия высших учебных заведений: Геология и разведка)
The works is made on the base of the materials collected during two field phases (2013-2014) in the territory of the R-41-XX, XXI sheet (Amderma area). Visean-Serpuhovian bathyal sediments of Pai-Khoi Shale Belt are represented by Kara formation. In contrast to the underlying and overlying predominantly clayey-siliceous sediments, it is composed of carbonate rocks. This study is focused on composition and origin of the carbonate sediments of the Kara formation in North East Pai-Khoi and is based on the analysis of cyclic sedimentary rock associations - cyclothems. The upper part of the formation section encloses two cyclothem types: fourth type is a sedimentation sequence, which is adequate to the development cycle of hydrothermal structures («white smokers»); the fifth type is represented by so-caffed seeps or nucleuses of fluid flows leakage on continental margins. The deeper section is formed by the activity of the carbonated turbidites. Finally, the formational model of Kara formation (Mississippian period) of North East Pai-Khoi is constmcted, which is considered to be responsible of the sedimentation sequence.